Autonomic heart rate regulation during mild dynamic exercise in humans: insights from respiratory sinus arrhythmia - Sone, R; Tan, N; Nishiyasu, T; Yamazaki, F (Japanese journal of physiology, 2004)
To better understand the neural mechanism of heart rate (HR) regulation during dynamic exercise, the responses of HR and the magnitude of respiratory R-R interval variation were examined during exercise and recovery at mild intensities in humans. Eight subjects performed 3-min constant load cycle exercises in a semi-supine position at work rates of 25, 50, and 100 W. The respiratory interval was fixed at 4 s. Peak-to-valley variation in R-R interval caused by respiration was measured breath-by-breath and standardized for tidal volume (DeltaRRst, a noninvasive index of the degree of parasympathetic cardiac control). At all work rates the HR increased significantly from 2.5 s after the beginning of exercise (p <0.05) and decreased temporarily and slightly at around 15 s, and the DeltaRRst varied almost inversely. The HR and the DeltaRRst until 12.5 s after the beginning of exercise changed independently of work rate (ANOVA, p=0.27 and p=0.08). The HR-DeltaRRst relationship at the initial phase of exercise (for 12.5 s) was almost the same at all work rates. These results suggest that the initial HR response to exercise is strongly parasympathetically regulated independently of work rate. The HR recovered slower than the DeltaRRst at 50 and 100 W. On the HR-DeltaRRst relationship, the HR during recovery was significantly higher than during exercise at 1/3, 1/2, and 2/3 levels of pre-exercise DeltaRRst at 50 and 100 W and at the 1/3 level at 25 W (p < 0.05). At 25 W, the difference in HR at the 1/3 level was 5.5 beats.min(-1), and the HR increase to exercise was 21.2 beats.min(-1). We suggest that a HR regulatory system responds slower than a cardiac parasympathetic system to exercise, a cardiac sympathetic system, is activated even during mild exercise in humans.